Study of physiological and biochemical variability of the moss Amblystegium serpens (Hedw.) Schimp. under the impact of heavy metals (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
Physiological and biochemical changes in Amblystegium serpens under different concentrations of lead and mercury are analyzed. Sublethal concentrations of these metals mainly cause quantitative changes in spectra of acid soluble proteins and of esterase multiple molecular forms. It is established that moss samples from places of different levels of pollution differed in amount of lead absorbed in gametophores. This fact can be explained by that plants more resistant to heavy metals may survive and be selected in polluted territories temperature is found to protect moss studied from the toxic impact of heavy metals. This suggests that proteins of thermal shock may play important role in normalization of esterase isozyme spectrum changed by lead and mercury impact.
Keywords: moss, heavy metals, acid proteins, multiple molecular forms of esterase.